Comparing Millennials With Their Predecessors Regarding Online Travel Behaviours: A Logistical Regression Modelling Approach - Amaro, Suzanne (2017)
Millennials, also known as Generation Y, are characterized by their use of technology, which is an integral part of their lives. Research has shown that they are different from earlier generations regarding their behaviours and attitudes. This article investigates and compares the behavior of Millennials with those of previous generations using data collected among 1,732 Worldwide Internet users. In order to understand what differentiates Millennials, this study considers several characteristics related with the way travelers use and perceive online resources to exchange information and buy travel products. Logistic Regression was applied to identify which factors independently discriminate between the two groups and the area under the receiver operator characteristic (ROC) curve, known as AUC, was used to assess the discriminative ability of the model. To select the variables to be considered in the multivariate logistic regression modelling stage, a univariate comparison was conducted. All significant variables were included in the multivariate analysis, significant being measured as having a p-value<0.05. Furthermore, because some non-significant variables may constitute an important contribution in the presence of other variables, all variables with p-value<0.1 were also considered for inclusion in the regression model. Forward step analysis was then used to find the final model, identifying a set of variables that independently contribute to differentiate the two groups. A distribution-free approach which aims to find the best linear combination that maximizes the AUC was also applied. The study found that, when compared with their predecessors, Millennials are more involved with travel social media and have a higher estimation to purchase travel online. Millennials behaviours may be an indication of the way people will behave in the future (Bolton et al., 2013). Therefore, it is crucial that Marketers and retailers better understand this young generation. This study provides useful insights, with indications of which factors matters most to Millennials in the online travel domain.